ACR Appropriateness Criteria® Local Excision in Early Stage Rectal Cancer. (October 2015) - Russo, Suzanne; Blackstock, A. William; Herman, Joseph M.; Abdel-Wahab, May; Azad, Nilofer; Das, Prajnan; Goodman, Karyn A.; Hong, Theodore S.; Jabbour, Salma K.; Jones, William E.; Konski, Andre A.; Koong, Albert C.; et al.
<x xml:space="preserve">Abstract</x> Low anterior resection or abdominoperineal resection are considered standard treatments for early rectal cancer but may be associated with morbidity in selected patients who are candidates for early distal lesions amenable to local excision (LE). The American College of Radiology Appropriateness Criteria are evidence-based guidelines for specific clinical conditions that are reviewed every 3 years by a multidisciplinary expert panel. The guideline development and review include an extensive analysis of current medical literature from peer reviewed journals and the application of a well-established consensus methodology (modified Delphi) to rate the appropriateness of imaging and treatment procedures by the panel. In those instances where evidence is lacking or not definitive, expert opinion may be used to recommend imaging or treatment. The panel recognizes the importance of accurate staging to identify patients who may be candidates for a LE approach. Patients who may be candidates for LE alone include those with small, low-lying T1 tumors, without adverse pathologic features. Several surgical approaches can be utilized for LE however none include lymph node evaluation. Adjuvant radiation±chemotherapy may be warranted depending on the risk of nodal metastases. Patients with high-risk T1 tumors, T2 tumors not amenable to radical surgery may also benefit from adjuvant treatment; however, patients with positive margins or T3 lesions should be offered abdominoperineal resection or low anterior resection. Neoadjuvant radiation±chemotherapy followed by LE in higher risk patients results in excellent local control, but it is not clear if this approach reduces recurrence rates over surgery alone.